The Correlation Between Sarcopenia And Transthyretin Levels Among Community-Dwelling Older Adults In Padang, West Sumatra - R. Ifan Arief Fahrurozi; Rose Dinda Martini; Roza Mulyana; Fandi Triansyah (Eduvest - Journal of Universal Studies, 2024)
The objective of this study was to evaluate the correlation between sarcopenia and transthyretin levels among community-dwelling older adults in Padang. This study employed a cross-sectional design and included 45 community-dwelling individuals aged 60 years and above who visited Andalas Primary Health Care in Padang, West Sumatra, Indonesia. Characteristics of sociodemographic and lifestyle habits were collected using a general questionnaire. Sarcopenia was defined in accordance with the criteria set forth by the Asian Working Group for Sarcopenia (AWGS) criteria encompass three components: low muscle mass, as determined by an index of appendicular skeletal mass/height2 less than 7,0 kg/m2 for males and less than 5,7 kg/m2 for females; low physical performance, as indicated by a gait speed less than 1,0 m/s; low muscle strength, defined as handgrip strength less than 26 kg for males and less than 18 kg for females. Accordingly, sarcopenia was defined as the presence of low muscle mass in conjunction with low physical performance and/or low muscle strength. Transthyretin levels were considered as independent variables in order to evaluate the potential correlation between transthyretin and sarcopenia status using bivariate analysis. The overall prevalence of sarcopenia was 51.1%, with four cases (40%) observed in males and 19 cases (54.3%) in females classified as having sarcopenia. The prevalence of sarcopenia was significantly lower among participants with normal nutritional status. A comparison of the participants with and without sarcopenia revealed that the former exhibited higher levels of transthyretin (p = 0,000).